Peran Manajemen Humas dalam Meningkatkan Loyalitas Publik di Lingkungan Sekolah Studi Literatur - Puspitasari, Ni Luh Gede Dian; Kristianti, Diyah Ayu; Shofiyyah, Alya; Warman, Warman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to examine the role of public relations management in increasing public loyalty in the school environment through a literature review. The results of the analysis show that public relations plays a strategic role as a liaison between schools and the public by focusing on information transparency, use of social media, increasing community participation, crisis management, and creating a positive image. This strategy has been proven to be able to increase public trust and support for schools, which is the main foundation for building loyalty. However, there are several challenges, such as low public relations professionalism, limited resources, and suboptimal use of technology. This literature study recommends increasing the capacity of public relations through training, optimizing digital media, and supporting school management to increase the effectiveness of the role of public relations.